Radioluminescence properties of the CdSe/ZnS Quantum Dot nanocrystals with analysis of long-memory trends - Nikolopoulos, D.; Valais, I.; Michail, C.; Bakas, A.; Fountzoula, C.; Cantzos, D.; Bhattacharyya, Debabrata; Sianoudis, I.; Fountos, G.; Yannakopoulos, P.; Panayiotakis, G.; Kandarakis, I. (Elsevier, 2016)
This paper reports radioluminescence properties of the CdSe/ZnS quantum dots. Three quantum dot samples were prepared with concentrations 14.2 × 10−5 mg/mL, 21.3 × 10−5 mg/mL and 28.5 × 10−5 mg/mL, respectively. The ultraviolet induced emission spectra of CdSe/ZnS dots exhibited a peak at 550 nm ranging between 450 nm and 650 nm. Discrepancies observed between 250 nm and 450 nm were attributed to the solvent and cuvette. The absolute efficiency calculated from random fractional-Gaussian luminescence segments varied. Long-memory fractional-Brownian segments were also found. The quantum dot solution with concentration of 21.3 × 10−5 mg/mL exhibited the maximum absolute efficiency value at 90 kVp. The CdSe/ZnS dots have demonstrated potential for detection of X-rays in the medical imaging energy range.
Keywords: Quantum dots; Absolute luminescence efficiency; CdSe/ZnS